Glycemic control in minks with tendency to obesity in the perinatal period with the use of HbA1C - Wencel, Hanna Bis; Rowicka, Agnieszka; Klimek, Kamila; Dębek, Bożena Nowakowicz; Wlazło, Łukasz; Bryl, Monika; Trawińska, Beata; Bełkot, Zbigniew (Brazilian Journal of Animal Science, 2018)
The objective of this study was to investigate the usefulness of HbA1C as a test in monitoring the long-term glycemic control during the perinatal period in minks with the tendency to obesity. On the scanbrown mink farm, screening research on one-year-old females showing predilections to obesity was conducted. In the first year of the experiment, 120 females were assessed using body condition score (BCS) system. The two groups that differed significantly in body weight were selected based on the BCS system and then two treatment groups of 30 females were formed: BCS II (lean) and BCS IV (thick). The groups were subjected to tests during the two years of the experiment. The biological material was urine and blood taken from vena safena five times a year. In whole blood, the level of glycosylated hemoglobin A1C was determined by ion exchange chromatography with chromatographic-spectrophotometric test (BioSystems S.A. company). Plasma glucose level was determined using Cormay reagents and BS 130 apparatus. The level of glucose in urine was also determined using diagnostic Medi-Test Combi 10 VET strips. The results were statistically analyzed using the SAS Enterprise Guide 5.1. The descriptive statistics and the analysis of one-way variance (ANOVA) were used. Statistically significant differences were analyzed by Tukey test at the significance level α = 0.05. Glycosuria was found in females in all studied stages of the production cycle. In both BCS II and BCS IV, hyperglycemia was observed in late lactation and decreased after weaning. Average concentrations of HbA1C reached values from 3.64 to 5.17%. HbA1C is a useful test for monitoring glycemic control that is why the presented research should be continued due to the lack of reference values in case of HbA1C in minks, which can contribute to making the diagnosis and help in confirmation or exclusion of diabetes
Keywords: body condition score; glucose; glycosylated hemoglobin; Neovison vison